Evidence-Informed Deliberative Processes for Legitimate Health Benefit Package Design − Part I: Conceptual Framework - Rob Baltussen; Maarten Jansen; Wija oortwijn (Kerman University of Medical Sciences, 2022)
Background  Countries around the world are increasingly rethinking the design of their health benefit packages to achieve universal health coverage (UHC). Health technology assessment (HTA) bodies support governments in these decisions, but employ value frameworks that do not sufficiently account for the intrinsically complex and value-laden political reality of benefit package design.Methods  Several years ago, evidence-informed deliberative processes (EDPs) were developed to address this issue. An EDP is a practical and stepwise approach for HTA bodies to enhance legitimate health benefit package design based on deliberation between stakeholders to identify, reflect and learn about the meaning and importance of values, and to interpret available evidence on these values. We further developed the conceptual framework and initial 2019 guidance based on academic knowledge exchange, analysing practices of HTA bodies, surveying HTA bodies and experts around the globe, and implementation of EDPs in several countries around the world.Results  EDPs stem from the general concept of legitimacy, which is translated into four elements - stakeholder involvement ideally operationalised through stakeholder participation with deliberation; evidence-informed evaluation; transparency; and appeal. The 2021 practical guidance distinguishes six practical steps of a HTA process and provides recommendations on how these elements can be implemented in each of these steps.Conclusion  There is an increased attention for legitimacy, deliberative processes for HTA and health benefit package design, but the development of theories and methods for such processes remain behind. The added value of EDPs lies in the operationalisation of the general concept of legitimacy into practical guidance for HTA bodies.